What the high altitude chamber can do for an endurance athlete
Elite, professional and serious athletes in training for endurance sports competition can use the SST High Altitude Chamber as a safe, legal and ethical way to stimulate EPO production, raise hematocrit, and VO2 max. Instead of traveling to a remote location for high altitude training, a competitive athlete can spend 4 to 8 hours per day in our comfortable, transparent hypobaric chamber which simulates a high altitude environment up to 15,000 feet. Then train at low or base altitude - the proven live high - train low regimen. What The High Altitude Chamber Can Do for an Endurance Athlete? The SST High Altitude Chamber replicates both the total, or absolute pressure and the oxygen partial pressure (PO2) experienced at altitude. When an athlete exercises at sea level (or base altitude) and rests or sleeps 4 to 8 hours/day in the Chamber for at least 2 weeks (progressing incrementally to 14,500 feet) the following physiological changes can occur: Generate erythropoietin (EPO) and raise blood hematocrit Increase red blood cell mass and total blood volume Boost vascular system capacity and blood oxygenation Improve oxygen transport Enhance capillary function and stimulate new capillary growth Produce new mitochondria Increase VO2 max Speed up metabolism Experience greater aerobic and anaerobic capacity Shorten recovery time following heavy exertion